The Effect of Global Company Animosity on Global Brand Attitudes in Emerging and Developed Markets: Does Perceived Value Matter?. Issue 2 (June 2013) - Alden, Dana L.; Kelley, James B.; Riefler, Petra; Lee, Julie A.; Soutar, Geoffrey N.
Country-level animosity effects on foreign products from disliked countries are fairly well understood, but little is known about the role of global company animosity (GCA). Such understanding is important in a world increasingly dominated by global brands that are rapidly losing their associations with individual countries. This study proposes a nomological net that features GCA and perceived value of global brands (PVGB) as "dual process antecedents" to global brand attitudes and mediators of four relevant exogenous constructs (consumer ethnocentrism and localism through GCA and cosmopolitanism and materialism through PVGB). Using nonstudent consumers, the authors test the model in three diverse national markets ranging from emerging to developed: Brazil, South Korea, and Germany. The results show support for the importance of PVGB as a counterbalance to GCA in Brazil and Germany. The dominance of the PVGB path in South Korea is due to the country's unique socioeconomic milieu. Although replication is warranted, international marketing managers should benefit from strategic consideration of the antecedents and pathways from GCA and PVGB to global brand attitudes.